Use of a Polyetheretherketone Clasp Retainer for Removable Partial Denture: A Case Report - Tetsuo Ichikawa; Kosuke Kurahashi; Lipei Liu; Takashi Matsuda; Yuichi Ishida (MDPI AG, 2019)
Clasp retainers made of metal alloys may be esthetically unappealing or cause allergic reactions. To investigate alternative materials, we used the nonfiller polyetheretherketone (PEEK) to fabricate the clasp retainer of a removable partial denture for the mandibular bilateral distal free-end abutment of an 84-year-old female. Two years later, few color and texture changes of PEEK were found macroscopically. The rest part and the clasp arm fitted well without any deformation. There were no particular occlusal or periodontal problems. Subjective satisfaction was expressed by both the practitioner and the patient.